Depositional Environment of Shallow-Marine Sandstones from Outcrop Gamma-Ray Logs, Belait Formation, Meragang Beach, Brunei Darussalam - Numair Ahmed Siddiqui, Mohamed Ali EL-Ghali, Abdul Hadi bin Abd , . (2016)
The outcrop of shallow marine sandstone, Belait formation at Meragang Beach, Brunei Darussalam have long been regarded as tide-, wave-and storm-dominated environment that reveals the reservoir heterogeneities and variation in sand body geometry. Intensive outcrop study methods were available from previously conducted work on Belait Formation.